Thriving in the dark: a new record and new species of Annelida (Lamarck, 1802) from a Balearic anchialine cave (Western Mediterranean Sea) - CAPA , MARÍA; MARTÍNEZ , ALEJANDRO; PONS , JOAN; GIL , JOÃO; MARTIN , DANIEL (Mediterranean Marine Science, 2025)
Anchialine caves are singular aquatic environments of significant conservation interest, defined by darkness, constant temperature, and low levels of nutrients and dissolved oxygen, as well as vertically stratified water layers. Due to their challenging accessibility, these caves represent one of the few remaining unexplored frontiers on Earth, hosting short-range endemics and ecologically specialized communities highly susceptible to anthropogenic disturbances. Exploration of a cave in the northern region of Mallorca, Balearic Islands (Western Mediterranean), has revealed the presence of a new genus and species of Polynoidae, Pollentia perezi Capa, Pons & Jaume, 2022, with presumed deep-sea affinities. Further exploration of this cave system showed two additional polychaetes. The first is a new species of Polycirrus (Terebellidae), whereas the second, Vermiliopsis labiata (Costa, 1861) (Serpulidae), previously known to inhabit marine environments, represents the first record of this species in an achialine cave. Notably, neither the terebellid nor the serpulid exhibits apparent morphological adaptations to their cave habitat. Our study combines morphological and molecular analyses to characterise the polychaete fauna of the Cova des Bastons, Mallorca, and increases the number of taxa associated with Mediterranean anchialine environments.